Mustahik Shift Strategy in Forming Muzakki Through an Independent Family Program at The Al Falah Social Fund Foundation in Jember - Mohammad Ilham; Moch. Chotib; Nurul Widyawati IR (International Journal of Economics, Business and Innovation Research, 2024)
The Muslim population of Jember Regency has considerable potential in terms of zakat regulation. This is illustrated in a study of the "Three Circles Model Revitalization" of zakat management institutions in which can provide an overview of zakat regulation in Jember Regency. The Independent Family Program is a program that is featured by the Al- Falah Jember Social Fund Foundation in order to create a prosperous and empowered society, and has a high entrepreneurial spirit without ignoring religious norms. In the context of this initiative, the object of this research is the Independent Family Program of the Al-Falah Jember Social Fund Foundation, one of the programs that contributes to raising the degree of humanity and helping to increase the income of its members through micro, small and medium enterprises. The focus of this research How is the effort to implement the Al-Falah Jember Social Fund Foundation to turn mustahik into muzakki through the Independent Family Program in developing creative businesses owned by mustahik? and how is the Implication of the Independent Family Program on the status of mustahik at the Al-Falah Jember Social Fund Foundation? The approach used in this research is a qualitative approach, with a descriptive type of presentation.